MANAGEMENT INFORMATION SYSTEM OF EMPLOYEE SELF SERVICE (ESS) AS AN EFFORT TO INCREASE HUMAN RESOURCE SECTION PERFORMANCE CITY SUBREGIONAL POLICE BANDUNG IN PANDEMIC COVID-19 - Rahmayanti, Rima; Hamdani, Dani; Hermawan, Wawan Budi (CENTRAL ASIA AND THE CAUCASUS, 2022)
The development of technology in the 4.0 era also facilitates administration and operations, so it can help with human resource data management in Bandung City Regional Police. In order to follow the medical procedure, personnel operations can be done online without going to the office and personnel department of the Bandung city police department, such as permits and leave, overtime.This study uses the Software Development Lifecycle (SDLC) method. The SDLC model was chosen because it has the advantage of being able to identify problems with older systems in more detail and determine the need for a well-developed new system. The SDLC model used in this study is the waterfall model. The waterfall model is called a waterfall because it has to go through stages to wait for the previous steps to finish and work in sequence.Based on the result of the system analysis that was running so it is proposed to design a new system, where the new system was expected could handle some problems. In modeling the new system, the author uses UML (Unified Modeling Language). With this ESS, employees can make the process easier administration such as requesting leave, etc. Because they can apply for administration at any time as long as there is an internet connection.